Association of advanced glycation end-product accumulation with overactive bladder in community-dwelling elderly: A cross-sectional Sukagawa study - Kenji Omae; Noriaki Kurita; Sei Takahashi; Shingo Fukuma; Yosuke Yamamoto; Shunichi Fukuhara (Asian Journal of Urology)
Objective: This study aimed to evaluate the influence of advanced glycation end-product (AGE) accumulation on the prevalence and severity of overactive bladder (OAB) in community-dwelling elderly adults. Methods: We conducted a cross-sectional study involving 269 Japanese community dwellers aged ≥75 years in 2015. AGE accumulation was non-invasively measured via skin autofluorescence (SAF) values using AGE Reader. The primary and secondary outcomes were the presence and severity of OAB evaluated using the Overactive Bladder Symptom Score (OABSS). Individuals with an urgency score of ≥2 and sum score of ≥3 were considered to have OAB. The associations of SAF with the prevalence and severity of OAB were assessed using logistic and linear regression models, respectively, adjusted for clinically important confounders. Results: The median age of participants was 78 years. Of 269 participants, 110 (40.9%) were men and 75 (27.9%) had OAB. The median SAF was 2.2 arbitrary units (AUs). Increasing median SAF was observed with increasing age. Multivariable analysis revealed that SAF was not associated with either the likelihood of having OAB (odds ratio per AU=0.77, 95% confidence interval: 0.37–1.62) or the natural log-transformed OABSS (β per AU=−0.07, 95% confidence interval: −0.26–0.12). Conclusions: In this study, AGE accumulation, as assessed by SAF, was not associated with the prevalence and severity of OAB in Japanese community-dwelling elderly people aged ≥75 years.